An Old Chapmen's Standard Yard Measure from Ceres, Fife (Proceedings of the Society of Antiquaries of Scotland, 1923)
The artefact was the standard or gauge by which the ellwands (so called whether containing 36 or 37 inches) were tested and regulated. it is made of iron and has a hinge in the centre so that it can be folded over into half its real length. Between the flanges at each end its total length is exactly 36 inches. This standard was issued by the Chapmen of Fife, based upon the official dimensions, and by it the travelling Chapmen regulated the measuring rods they carried as they perambulated,\r sometimes on horseback, their several districts. False measures were stigmatised by the Societies, and the condemned ellwands (units of measurement) were destroyed.